2015
DOI: 10.1111/jog.12696
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity in women with polycystic ovary syndrome

Abstract: A considerable number of women with PCOS experience a psychiatric disorder during their lifetime. Clinicians should be aware that women with PCOS are at a high risk for major depression, generalized anxiety disorder, and binge-eating disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 33 publications
0
41
0
4
Order By: Relevance
“…Many studies demonstrated high rates of depression, between 40% and 60%, in women with PCOS (Kerchner et al, 2009). Depression and anxiety disorders were also found to be the most common comorbid psychiatric conditions in patients with PCOS in Turkey (Annagür et al, 2015). Both depressive and anxiety disorders were increased in the first year after a diagnosis of PCOS (Okamura et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Many studies demonstrated high rates of depression, between 40% and 60%, in women with PCOS (Kerchner et al, 2009). Depression and anxiety disorders were also found to be the most common comorbid psychiatric conditions in patients with PCOS in Turkey (Annagür et al, 2015). Both depressive and anxiety disorders were increased in the first year after a diagnosis of PCOS (Okamura et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Anecdotally, women with PCOS appear to have difficulty with diet and weight management. Lifestyle modifications are first‐line management for treatment of PCOS in overweight or obese women, and weight loss has been shown to improve menstrual regularity, cardio‐metabolic risk factors and androgen excess . Despite the association between PCOS and obesity, along with the role of diet and weight loss in treatment, limited data exist on the best intervention to achieve sustainable lifestyle modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have evaluated the relation between PCOS and psychiatric disorders; however, most have evaluated psychiatric symptoms based on self-report measures 1,3. There remains, therefore, an unclear relationship between PCOS and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%